Evolutionary ecology of virulence in a fish parasite - Mahmud, Muayad Ahmed (2016)
Virulence (parasite- induced host fitness reduction) is thought to correlate positively with pathogen reproduction rates, but its relationship with pathogen transmission is likely to be determined by a trade- off between the costs and benefits of harming hosts. This project aims to investigate factors which affect host-parasite interactions and particularly those which may play a role in virulence evolution. In doing so, it describes experiments carried out using a monogenean ectoparasitic flatworm (Gyrodactylus arcuatus) and its three-spined stickleback (Gasterosteus aculeatus) host. Populations of this fish species experience a range of both environmental and ecological conditions. Such environmental heterogeneity has been found to drive changes in fish phenotypic traits such as morphology, behaviour, life history and physiology which may consequently affect parasite fitness. I demonstrate that under these conditions, parasite strains from different host populations evolve variation in virulence levels. I also reveal that coevolution in this host parasite system is likely to lead to local adaptation of G. arcuatus at the host population level. I show that competition between parasite species sharing a single host leads to increased parasite reproduction rates, but it shortens the infection time which may be due to earlier stimulation of host immune responses. I show that virulence is neither influenced by the population density, immunity (epidermal mucus), social behaviour of fish hosts nor the natural parasite life expectancy. Lastly, I find that virulence in this system is negatively influenced by the density of stickleback predators and positively associated with loch water pH. Taken together, these results suggest that in this host parasite system, both ecological and environmental factors which drive phenotypic changes in fish hosts may evolutionarily feedback to affect parasite virulence.